Attribution and attributional processes of organizations' environmental messages. (September 2021) - Shin, Sumin; Ki, Eyun-Jung
This experimental study, guided by attribution theory, investigated the impact of the substantiation and specificity of organizations' environmental messages on perceived communication motivation and how this perception prompts audiences' affective and cognitive responses. Findings showed that specific messages increased perceived intrinsic motivation, whereas vague messages increased perceived extrinsic motivation; in turn, perceived intrinsic motive positively influenced audiences' message attitude, organization attitude, message credibility, organization credibility, and organization's green image, whereas perceived extrinsic motive negatively influenced these aspects.